THE ROLE OF EDUCATION AND IDEOLOGY IN THE EDUCATION OF YOUTH IN THE SPIRIT OF PATRIOTISM - O.Sh. Yuldashev (Bright Mind Publishing, 2025)
This article is dedicated to the role of the education system and ideology in the upbringing of youth in the spirit of patriotism. The article scientifically analyzes the importance of education in shaping national ideas, national values, and the sense of patriotism among the youth. It also emphasizes the significant role ideological influences play in shaping the thinking and social activity of young people. The article discusses the importance of government policy and the practices of educational institutions in the upbringing of youth.
Keywords: youth upbringing, patriotism, national idea, ideology, spiritual and moral development, state policy, educational institutions, cultural heritage, national values, love for the homeland, social activity, and globalization.